2018
DOI: 10.12928/telkomnika.v16i1.6727
|View full text |Cite
|
Sign up to set email alerts
|

A Radial Line Slot Array (RLSA) Antenna with the Specifications of 16 dBi Outdoor patch Antenna

Abstract: It is recommended by several researches that RLSA antennas have possibility as an option for Wi-Fi devices antennas. Therefore, to dig deeper this possibility, we designed a RLSA antenna that mimics the specification of an antenna usually found in market, that is 16 dBi outdoor patch antenna. We carried out a parameterization to get a best RLSA antenna model. The model was then fabricated and measured. The measurement results are quite agrees with the simulation results. We found that with the same size of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…We observe that although the area of the half RLSA is the smallest, the gain is still the best. As an example, compared to the antenna in the study [22], the area of the half RLSA is 5.74 times smaller. Since, theoretically, the gain should decrease linearly with the decrease of the area, the gain of the half RLSA should be 5.74 times smaller, although in reality , it is only 4.47 times smaller.…”
Section: Comparison Of a Half Rlsa With Other Small Rlsa Antennasmentioning
confidence: 80%
See 1 more Smart Citation
“…We observe that although the area of the half RLSA is the smallest, the gain is still the best. As an example, compared to the antenna in the study [22], the area of the half RLSA is 5.74 times smaller. Since, theoretically, the gain should decrease linearly with the decrease of the area, the gain of the half RLSA should be 5.74 times smaller, although in reality , it is only 4.47 times smaller.…”
Section: Comparison Of a Half Rlsa With Other Small Rlsa Antennasmentioning
confidence: 80%
“…Using this method, small RLSA antennas with a radius of 75 mm and at a frequency of 5.8 GHz could be designed without high reflection coefficients, which other techniques could not achieve previously. Several studies have also reported this technique's success in the development of small low-reflection antennas for the Wi-Fi market [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…We also chose polypropylenes as the dielectric material for the antenna. The material of copper and polypropylenes were chosen based on the successfully of their using in previous researches [21][22][23][24][25][26]. The values of all the material of antenna are listed in Table 2.…”
Section: Researchmentioning
confidence: 99%
“…This technique also successfully minimizes the reflection coefficient [22]. Due to this success, Purnamirza recommended their technique to be implemented in designing small RLSA antennas [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Purnamirza introduced extreme beam squint technique to efficiently radiate power through slots, which significantly reduces power reflections [16]. This also led to the successful implementation of this technique to design several small Wi-Fi RLSAs for market needs [17]- [22].…”
Section: Introductionmentioning
confidence: 99%